Pre-Marital Seclusion (Kahiya) from the Perspective of Islamic Law (Study of Wambuloli Village, Central Buton) - Siti Salmawati Hada. N; La Hanuddin; Rahmad Haniru (Social Science Academic, 2026)
The tradition of seclusion (kahiya) prior to marriage is still practiced by the community of Wambuloli Village, Central Buton Regency, as part of customary norms aimed at preserving the honor and preparedness of prospective brides. However, in its implementation, several customary practices raise concerns regarding their conformity with the principles of Islamic law. This study aims to analyze the forms of implementation of the seclusion (kahiya) tradition and to examine these practices from the perspective of Islamic law. This research employs a qualitative method with a normative-empirical approach. Data were collected through observation, structured interviews, and documentation involving traditional leaders, religious figures, and women who underwent the seclusion process. The data were analyzed using descriptive-analytical techniques through the stages of data condensation, data display, and conclusion drawing. The findings indicate that the seclusion tradition contains positive values, including the preservation of honor and the mental preparation of prospective brides; however, certain practices such as the neglect of religious obligations and specific symbolic beliefs potentially conflict with the principles of Islamic law. This study concludes that the seclusion tradition may continue to be preserved provided that adjustments are made to ensure alignment with the principles of public benefit (maslahah) and the fundamental values of Islamic law. This research emphasizes the importance of dialogue between customary traditions and religion in maintaining a balance between cultural preservation and the application of Islamic law.